WP lavori in corso. / thirty years of research in style. - Cloudsdale, leanne (New York : Rizzoli International Publications, 2013)
"This lavish volume celebrates thirty years of WP Lavori in Corso, a prestigious Italian company dedicated to researching, redefining, and cultivating the best heritage brands from all over the world. Since its founding in Bologna in 1982, WP Lavori in Corso's success has always rested on the scouting and selection, across the globe, of apparel brands and products marked by a long history, strong tradition, outstanding quality, and innovation. The company initially licensed and distributed brands such as Barbour, Woolrich, and Blundstone in Italy and now has grown to become these brands' invaluable collaborator, working with internationally renowned designers and creative directors to start new global trends and produce contemporary designs and styles, while also remaining true to the brands' history and heritage. This beautifully illustrated and designed book, curated and edited by Inventory, features photographs of the fashion brands WP distributes, its advertising campaigns, catalogs, and impeccably styled stores"--Publisher's web site.
Includes advertising images for Woolrich John Rich & Bros. WP Lavori in Corso obtained the license for the historic Woolrich brand in the 1990s.
boek
Keywords: Lavori In Corso